2007
DOI: 10.1080/02652030701242566
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in cereal and cereal products: A review on progress in level reduction

Abstract: In March 2006, a joint workshop was organized by the European Commission and the Confederation of EU Food and Drink Industries (CIAA) to discuss current knowledge and achievements in the reduction of acrylamide levels. This paper focuses on the progress made with cereal products. At present, the reduction options available are applicable to a limited number of cereal products and are product-specific. The following are the most promising: * Adjustment of time and temperature during baking. * Extend fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 31 publications
0
62
1
Order By: Relevance
“…Cultivars with low reducing sugars were more suitable for potato products, cooked or processed at high temperatures [29]. Konings et al [28] established the significant impact of fertilizer application rate on ACR levels mainly due to differences in crude protein and asparagine and contents. A study by Claus et al [38] demonstrated the effect of nitrogen-based fertilizers in causing high amounts of protein and amino acid.…”
Section: Agronomic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cultivars with low reducing sugars were more suitable for potato products, cooked or processed at high temperatures [29]. Konings et al [28] established the significant impact of fertilizer application rate on ACR levels mainly due to differences in crude protein and asparagine and contents. A study by Claus et al [38] demonstrated the effect of nitrogen-based fertilizers in causing high amounts of protein and amino acid.…”
Section: Agronomic Factorsmentioning
confidence: 99%
“…While these precursors affect ACR formation, the presence of other compounds that compete with amino acids and reducing sugars in the Maillard reaction are also vital compositional factors [21]. In potato and cereal products, ACR levels are highly correlated with glucose/fructose and asparagine concentrations [28]. Varieties in crop cultivar could also affect the reducing sugar content in the produce [29].…”
Section: Substrate Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In March 2006, the European Commission and the Confederation of EU Food and Drink Industries (CIAA) organized a joint workshop to discuss current knowledge and achievements in the reduction of acrylamide levels (Konings et al, 2007). Acrylamide toxic exposure prevention should aim to avoid inhalation, dermal uptake or ingestion of food sources of this substance (Keramat et al, 2011).…”
Section: Epidemiological Evidence Of Risk From Consumption Of Acrylammentioning
confidence: 99%